Long-term follow-up for pilonidal sinus surgery: A review of literature with metanalysis. Issue 5 (October 2018) - Milone, M.; Velotti, N.; Manigrasso, M.; Anoldo, P.; Milone, F.; De Palma, G.D.
Abstract: Background: Sacrococcygeal pilonidal sinus disease (PSD) is a common chronic inflammation of the natal cleft and presents as an abscess or a chronically discharging, painful sinus tract. The management of chronic PSD is variable, contentious, and problematic. Although many surgical procedures have been tried, the best surgical method remains controversial. The aim of this systematic review with meta-analysis of literature is to provide surgeons an objective instrument of decision through an analysis of recurrence rate of various surgical techniques in a long-term follow-up. Methods: Systematic literature searches were performed to identify all available studies. According to the pre-specified protocol, all studies reporting a surgical approach to PSD with a minimum follow-up of 5 years were included. Results: Fifteen studies were included in the analysis. The number of patients varied from 50 to 1165 with a mean follow-up from 58.36 to 240 months. The overall incidence of recurrence was of 0.138; the resulting incidence of open healing, midline closure and out-midline closure were of 17.9%, 16.8% and 10% respectively. Conclusions: Interestingly, our data reveal a rate of relapsing disease higher than the one defined in previous studies both for the overall PSD and for each surgical procedure. A long-term follow-up of at least 5 years, should be considered the gold standard in pilonidal sinus surgery benchmarking. From our results, we can state that open healing and midline closure should not be considered effective for their high frequency of relapse disease and midline primary closure should be preferred.